2020
DOI: 10.35542/osf.io/ux8hs
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Are we ready for Virtual Reality in K-12 classrooms?

Abstract: Virtual reality technology has existed since the late 1950s; however, its use in the educational sector has been limited because of the cost of the equipment, inaccessibility of the technology, issues of usability, and lack of appropriate educational content and educator training. New technological advances have resolved some of these limitations. Additionally, affordable virtual reality equipment that has been predominately used with adults shows compelling results, highlighting the potential of this technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…While there is growing evidence that interactive VR applications can have educational benefits (Araiza-Alba et al, 2020;Merchant et al, 2014;Mikropoulos & Natsis, 2011) [Author (2020).To be added following double blind review], studies using 360° VR videos with children for educational or training purposes are less common. However, two recent studies using 360° panoramas (virtual field trips) using VR HMD suggest that motivation, presence and engagement can be enhanced by the use of this technology (Cheng & Tsai, 2019;Han, 2019).…”
Section: The Use Of 360° Vr Videos In Educationmentioning
confidence: 99%
“…While there is growing evidence that interactive VR applications can have educational benefits (Araiza-Alba et al, 2020;Merchant et al, 2014;Mikropoulos & Natsis, 2011) [Author (2020).To be added following double blind review], studies using 360° VR videos with children for educational or training purposes are less common. However, two recent studies using 360° panoramas (virtual field trips) using VR HMD suggest that motivation, presence and engagement can be enhanced by the use of this technology (Cheng & Tsai, 2019;Han, 2019).…”
Section: The Use Of 360° Vr Videos In Educationmentioning
confidence: 99%
“…In their own meta-analysis, Coban et al (2022) , considered fourteen previous meta-analyses and 105 independent ESs (Effect Sizes) from 48 primary studies: They found an overall ES of g = 0.38, which corresponds to a small to medium positive effect. Araiza-Alba et al (2020a , b) arrived at a similar conclusion concerning the use of desktop VR and IVR with children.…”
Section: Introduction and Goalmentioning
confidence: 56%
“…Finally, no statistically significant difference between non-immersive VR and immersive VR shares a critical insight into VR resource selection for teachers and school administrators. While immersive technology provides users with the most realistic experience, the costs associated with HMDs and possible health concerns can be barriers to integrating VR with children (Araiza-Alba, Keane, & Kaufman, 2022; Park et al, 2019). The study found not much difference in terms of knowledge development, classroom engagement, and historical empathy development between immersive VR and non-immersive VR.…”
Section: Discussionmentioning
confidence: 99%
“…Park and her colleagues (2019) also reported other health concerns with the use of VR including dry eyes, headaches, and sweating. VR device manufacturers restrict using the device with children under the age of 13 years although they have not provided a rationale for such age restrictions (Araiza-Alba, Keane, & Kaufman, 2022). Interestingly, Tychsen and Foeller (2020) assessed visuomotor effects of VR headset use among 50 children aged 3–10 years old and concluded, “Young children tolerate fully immersive 3D virtual reality game play without noteworthy effects on visuomotor functions….…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation